2016
DOI: 10.1177/1357633x16647894
|View full text |Cite
|
Sign up to set email alerts
|

Systematic thematic review of e-health research in the Gulf Cooperation Council (Arabian Gulf): Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and United Arab Emirates

Abstract: Introduction The Gulf Cooperation Council (GCC or 'Arabian Gulf'), comprising Bahrain, Kuwait, Oman, Qatar, Saudi Arabia and United Arab Emirates, is a political organization sharing a common history and culture. All GCC nations have made substantial investments in telecommunications and electronic health infrastructure since 2000. Methods We conducted a literature search in English and Arabic on peer-reviewed e-health research up to December 2014 originating in the GCC. The objective was to retrieve all resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 23 publications
3
18
0
Order By: Relevance
“…We identified important research gaps in digital health research based on our scientometric analyses (Figure 7), also corroborated by previous research (10,26): a) Trial data: We found a lack of controlled trials of medical devices, algorithms, and telemedicine technology in hospital centers in the Arab world. If we are to estimate precise effect sizes for these technologies, it is important to develop this field of research in these countries.…”
Section: Gaps In Research and Way Forwardsupporting
confidence: 86%
“…We identified important research gaps in digital health research based on our scientometric analyses (Figure 7), also corroborated by previous research (10,26): a) Trial data: We found a lack of controlled trials of medical devices, algorithms, and telemedicine technology in hospital centers in the Arab world. If we are to estimate precise effect sizes for these technologies, it is important to develop this field of research in these countries.…”
Section: Gaps In Research and Way Forwardsupporting
confidence: 86%
“…In parallel, the World Health Organization has produced a web-based intervention called “Step-by-Step” to treat symptoms of depression, which is currently being tested in Lebanon with cultural and contextual adaptations [ 36 ]. Similarly, in Saudi Arabia, a 10-year national eHealth program was launched in 2011 with the aim of developing clinical automation, telecommunication infrastructure, and a nationwide eHealth record system [ 43 ]. In Egypt, the use of online consultations in specific fields, such as dermatology and psychiatry, is starting to develop [ 28 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the current levels of adoption and maturity of health informatics solutions in Kuwait are limited (Weber et al, 2017). While some hospitals have some electronic solutions such as EHRs or laboratory information system, these solutions are operating in a silo and do not interface with other Additionally, healthcare institutions should be involved in continuous assessments to uncover their digital health maturity.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted from the surveyors’ comments, organisations that adopted and deployed integrated informatics solutions, such as EHRs, had better scores compared with their peers who did not. However, the current levels of adoption and maturity of health informatics solutions in Kuwait are limited (Weber et al, 2017). While some hospitals had some electronic solutions such as EHRs or laboratory information system, these solutions were operating in a silo and did not interface with other systems in or outside the hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation